Delving into Secondary School EFL Teachers’ Practices Facilitated by Task-Based Language Instruction - Syla Rrita (SEEU Review)
The implementation of Task-Based Instruction (TBI) has resulted in a productive transformation for many foreign language teachers, since it emphasizes the importance of context and meaningful language use. This study presents an overview of the Task-Based Instruction, provides a framework and elaborates task characteristics. It investigates secondary school EFL teachers’ experiences with the task-based approach through semi-structured interviews. The results show that despite the fact that some teachers are not trained in Task-Based Teaching, they are eager to implement this approach due to the fact that it enhances the communicative competency and provides students with maximized ways of using the target language. The results show that this pedagogical transformation necessitates material adaptation, as well as careful task design, planning and preparation. As per the examination procedure, it is evident that task-based teaching is not created with examination in mind. Its aim is to support students in using English outside the classroom, even if the language they produce is not always grammatically accurate. It is possible to prepare learners for examinations through form-focused activities which are accompanied by tasks and later on reflected in the examination. Above all, Task-Based Instruction is concerned with learners’ ability to use language effectively. Therefore, this paper considers some key areas for future research, and it stresses the need for teacher training, in order for successful implementation to take place.